Immunology of Drug-Resistant Tuberculosis (DR-TB):A Literature Review - Oinike, Irene; Wijaya, Dewi (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2025)
Drug-resistant tuberculosis (DR-TB) poses significant challenges to control efforts due to its complex pathogenesis and limited treatment options. DR-TB arises through primary infection with resistant strains or secondary resistance during the course of treatment. Secondary resistance is divided into intrinsic and acquired. In intrinsic resistance, infection is caused by TB germs that have evolved, causing resistance through several mechanisms, namely reducing cell membrane permeability, drug reflux, degradation and target modification, while acquired resistance is caused by chromosomal mutations in target genes during the treatment process. Resistance is driven by chromosomal mutations in key genes such as rpoB, katG, inhA, pncA, emb, gyrA/gyrB, rrs and others, leading to reduced drug susceptibility. This review summarizes immunological mechanisms relevant to resistance and current treatment approaches.